2021
DOI: 10.2147/btt.s290305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of NK Cell-Based Therapeutics for the Treatment of Lung Cancer for Biologics: Targets and Therapy

Abstract: Lung cancer has a dismal prognosis and novel targeted therapies leave still room for major improvements and better outcomes. Immunotherapy targeting immune checkpoint (IC) proteins, either as single agents or in combination with chemotherapy, is active but responders constitute only approximately 10-15% of non-small cell lung cancer (NSCLC) patients. Other effector immune cells such as CAR-T cells or NK cells may help to overcome the limitations of the IC inhibitor therapies for lung cancer. NK cells can kill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 146 publications
(205 reference statements)
1
17
0
Order By: Relevance
“…The majority of the NK cell population in the lung is CD56 bright CD16 - , exhibiting high cytokine release but low cytotoxicity [ 48 ]. In fact, in vivo studies have demonstrated that human lung NK cells respond poorly to activation by target cells, when compared to peripheral blood NK cells.…”
Section: Nk Cells In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the NK cell population in the lung is CD56 bright CD16 - , exhibiting high cytokine release but low cytotoxicity [ 48 ]. In fact, in vivo studies have demonstrated that human lung NK cells respond poorly to activation by target cells, when compared to peripheral blood NK cells.…”
Section: Nk Cells In Nsclcmentioning
confidence: 99%
“…In fact, in vivo studies have demonstrated that human lung NK cells respond poorly to activation by target cells, when compared to peripheral blood NK cells. It has been proposed that this is due to the suppressive effects associated with alveolar macrophages and soluble factors that are present in the epithelial lining of the lower respiratory tract to maintain lung homeostasis [ 48 , 49 ]. These human lung NK cells share several phenotypic similarities with the decidual NK (dNK) cells present in the maternal decidua during pregnancy [ 50 ].…”
Section: Nk Cells In Nsclcmentioning
confidence: 99%
“…Purified NK cells had demonstrated evidence of therapeutic potential for a wide variety of human malignancies, including sarcomas [52], myeloma [53], carcinomas [54][55][56], lymphomas [57], and leukemia [1,58]. However, the clinical efficacy and application of NK cell immunotherapy have been limited by the inability to obtain sufficient cell numbers for adoptive transfer, as these cells represent a small fraction of peripheral white blood cells, expand poorly ex vivo, and have limited life spans in vivo.…”
Section: Characteristics Of Nk Cellsmentioning
confidence: 99%
“…Functionally, NK cells can produce cytokines that support T helper polarization and T cell activation, as well as stimulate dendritic cell (DC) and B cell maturation to bridge and orchestrate innate and adaptive immune responses (27). Hence, NK cells play an important role in tumor surveillance and can be manipulated by artificial activation techniques to present a highly effective anticancer tool against malignancies, and dependent on successful further rearming and mobilization, against solid tumors in the future (28). However, there are currently few studies on the relationship between the prognosis of stage I-IIIA NSCLC after resection and peripheral T-lymphocyte subsets combined with CD16+56 NK cells.…”
Section: Introductionmentioning
confidence: 99%